Impact of mobile app-based service on customer loyalty in food delivery organization: a case of Foodpanda - Sharika, Nishat Tasnim (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.